2012
DOI: 10.1016/j.mayocp.2011.09.004
|View full text |Cite|
|
Sign up to set email alerts
|

Recognition and Management of Nonrelaxing Pelvic Floor Dysfunction

Abstract: Nonrelaxing pelvic floor dysfunction is not widely recognized. Unlike in pelvic floor disorders caused by relaxed muscles (eg, pelvic organ prolapse or urinary incontinence, both of which often are identified readily), women affected by nonrelaxing pelvic floor dysfunction may present with a broad range of nonspecific symptoms. These may include pain and problems with defecation, urination, and sexual function, which require relaxation and coordination of pelvic floor muscles and urinary and anal sphincters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 38 publications
1
115
0
8
Order By: Relevance
“…It has been shown that vaginal delivery may cause pelvic floor dysfunction (PFD) by damaging pelvic support tissues such as muscles, connective tissues and nervous structures [2]. Patients with PFD present a variety of clinical scenarios, including lower urinary tract excretory and defecation dysfunction and prolapse of the female reproductive organs and pain [3, 4]. More than 30% of women suffer from PFD, depending on the different definitions of the disorder [1].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that vaginal delivery may cause pelvic floor dysfunction (PFD) by damaging pelvic support tissues such as muscles, connective tissues and nervous structures [2]. Patients with PFD present a variety of clinical scenarios, including lower urinary tract excretory and defecation dysfunction and prolapse of the female reproductive organs and pain [3, 4]. More than 30% of women suffer from PFD, depending on the different definitions of the disorder [1].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has greatest value in (1) excluding Hirschsprung's disease by the presence of a normal rectoanal inhibitory reflex and (2) supporting a clinical impression of defecatory disorders as evidenced by high anal resting pressures, typically ≥90 mm Hg (anismus), with relatively little voluntary augmentation, suggestive of a nonrelaxing pelvic floor/sphincter dysfunction 92 or an abnormal (ie, lower) rectoanal pressure gradient during simulated evacuation. The precise utility of a low rectoanal pressure gradient to diagnose defecatory disorders is unclear because there is considerable overlap in values for this parameter between asymptomatic subjects and patients with defecatory disorders.…”
Section: Diagnostic Testsmentioning
confidence: 94%
“…In many authors' opinions, this learned misresponse (paradoxical contraction) may be due to sexual, physical or emotional abuse, or resulting from a history of painful defecation during childhood [4,5].The pathophysiology of chronic constipation is heterogeneous; so, different physiological tests, such as "balloon expulsion test", "conventional defecography", electromyography (EMG) of the muscles of anal and pelvic floor can be used to identify the DD patients [6]. Each of these tests has its own limitations, thus, none can be used separately.…”
Section: Introductionmentioning
confidence: 99%